The effectiveness of rebranding towards TM: through advertising and reputation / Noor Asyikin Rohman - Rohman, Noor Asyikin (Faculty of Business and Management, 2007)
This thesis reports on a study that attempts to provide some insights about how effective the rebranding strategies being implement to TM. Branding is an effective marketing strategy tool that has been used with frequent success in the past. Today, branding is experiencing a new popularity resulting from new, innovative applications. Although there have been instances where branding has been less than successful, marketers are beginning to find the appropriate applications in a given setting. Issues and problems concerning branding strategy today include the selection of a brand name. This fundamental issue will impact on the success of a branding strategy. Once a name is selected, marketers have to choose the advertising strategy to support and communicate the name. Finally, keeping the brand in a strong position is a critical concern. New areas of branding include corporate, industrial, and service branding. These non-traditional branding environments are becoming the future for marketers using branding strategy. To add to the new branding areas, there are new branding techniques. These techniques include brand extensions and ingredient branding. New strategies, techniques, and arenas for branding have to be managed. The organization must support and identify with the strategy. The goals, objectives, and mission of any organization should be in line with the branding strategy employed.